2015
DOI: 10.1177/0952076715595676
|View full text |Cite
|
Sign up to set email alerts
|

Do public consultations work? The case of the Social Services and Well-being (Wales) Bill

Abstract: Conducting a public consultation is a popular way to draw on wider expertise in framing legislation in the UK. In Wales, low scrutinising capacity of a relatively small legislative chamber and limited civil service resources to prepare legislation may contribute to the popularity of consultations. Public consultations may also resonate with themes of inclusion and participation in Welsh governance. The Social Services and Well-being (Wales) Bill was the first large legislative project of the Welsh Government s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
1
18
0
4
Order By: Relevance
“…One notable exception is a 2014 study by Gilens and Page; their quantitative analysis of 1,779 public policy issues subject to public consultation in the US showed that 'when the preferences of economic elites and… organized interest groups are INSTITUTE FOR RESOURCES, ENVIRONMENT AND SUSTAINABILITY UNIVERSITY OF BRITISH COLUMBIA controlled for, the preferences of the average American appear to have only a minuscule, near-zero, statistically non-significant impact upon public policy' (575). Their results support other case-study analyses' findings of (economic) elite influence on public policy-making (J. Carr 2012; Kaehne and Taylor 2016;Parkins and Sinclair 2014). Studies also highlight government officials' role in limiting consultation's policy impact (Carvalho, Pinto-Coelho, and Seixas 2016;Cheeseman and Smith 2001).…”
Section: Outcome-based Evaluationssupporting
confidence: 79%
See 4 more Smart Citations
“…One notable exception is a 2014 study by Gilens and Page; their quantitative analysis of 1,779 public policy issues subject to public consultation in the US showed that 'when the preferences of economic elites and… organized interest groups are INSTITUTE FOR RESOURCES, ENVIRONMENT AND SUSTAINABILITY UNIVERSITY OF BRITISH COLUMBIA controlled for, the preferences of the average American appear to have only a minuscule, near-zero, statistically non-significant impact upon public policy' (575). Their results support other case-study analyses' findings of (economic) elite influence on public policy-making (J. Carr 2012; Kaehne and Taylor 2016;Parkins and Sinclair 2014). Studies also highlight government officials' role in limiting consultation's policy impact (Carvalho, Pinto-Coelho, and Seixas 2016;Cheeseman and Smith 2001).…”
Section: Outcome-based Evaluationssupporting
confidence: 79%
“…This focus on participatory engagement as key to good governance, and democracy broadly, has resulted in the institutionalization of consultation within public planning and policy-making (Shipley and Utz 2012), where submission-based consultation processes are a common means to solicit feedback, particularly in western democracies (Kaehne and Taylor 2016). The advent of the internet has transformed consultation, generating new mechanisms that enable broad, low-cost engagement through electronic platforms (Culver and Howe 2004).…”
Section: Participation In Environmental Policy-makingmentioning
confidence: 99%
See 3 more Smart Citations